Virulence assay on environmental originated strains of Pseudomonas aeruginosa - Kaszab, Edit; Pék, Nikoletta; Farkas, Milán; Kriszt, Balázs; Szoboszlay, Sándor (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
Opportunistic pathogen microorganisms are widespread in our natural environment however, their presence as a risk factor to human health only recently has been reported. One of these pathogen bacteria is the species Pseudomonas aeruginosa. P. aeruginosa due to a wide-range of catabolic activities has the ability to degrade various organic contaminants. With its adaptability to contaminations P. aeruginosa is able to reach an infective dose in hydrocarbon polluted soil or groundwater. Our investigations show that P. aeruginosa is widespread in hydrocarbon contaminated samples (primarily in soil and groundwater) and is able to become the dominant species among soil communities. Moreover, environmental originated strains can reach or exceed the clinically experienced level of haemolytic activity, namely have the ability to damage erythrocytes that is a direct virulence factor. It was established that environmental and clinical originated strains of P. aeruginosa cannot be distinguished with regard to their haemolytic activity, therefore the possible health risk of environmental originated strains is not less than the clinically detected level. These strains were isolated from various regions of Hungary, mainly from fields that are under strong antropogenic effects. Therefore, the presence and intensive growth of these pathogenic microorganisms can be attributed to human activities indirectly. To eliminate of these harmful effects and to prevent of the spread of pathogenic microbes are important tasks for environmental protection and for microbial ecological purposes as well.